Evaluation of subsidies for rangelands in development of sheep and goat farming - Cevher C.; Ataseven Y.; Altunkaynak B.; Köksal Ö; Coskun Cevher S. (Innovation for sustainability in sheep and goats, 2019)
The production of sheep and goat is heavily dependent on grazing for feed needs of livestocks in Turkey. This requires that the yield of fodder has to be increased to the level of meeting the livestocks’ needs. For this reason, rangelands are improved and put into service for breeders by government. It is aimed to provide a sustainable fodder yield on these rangelands. The effects of the improvement works on breeders and rangelands should be studied. This research is conducted in 11 villages where the most improvement works are carried out and implemented. The breeders who produce sheep and goat in villages are the population of the study and the sampling volume is determined according to these numbers. The sampling volume is fixed by 89, according to the Stratified Sampling Method. The data obtained are analyzed by Chi-square test and evaluated with regard to the analysis results. According to the study results, the correlation between the breeders’ view about finding rangelands improvement works successful and their age, level of education, land size and forage crops production are found statistically significant (p<0.05). In respect to sustainability, according to the analysis results; the correlation between the demand for the sustainable rangeland use and the variables of rangelands improvement works, producing forage crops and the low feed cost is found statistically significant (p<0.05). According to the analysis and evaluations, it is found that rangelands improvement works carried out in the study field are not successful and sustainable use of rangelands will not be realized in respect to socio-economic factors.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)